2019
DOI: 10.3390/children6100105
|View full text |Cite
|
Sign up to set email alerts
|

Social Functioning of Childhood Cancer Survivors after Computerized Cognitive Training: A Randomized Controlled Trial

Abstract: Childhood cancer survivors are at risk for cognitive and social deficits. Previous findings indicate computerized cognitive training can result in an improvement of cognitive skills. The current objective was to investigate whether these cognitive gains generalize to social functioning benefits. Sixty-eight survivors of childhood cancer were randomly assigned to a computerized cognitive intervention (mean age 12.21 ± 2.47 years, 4.97 ± 3.02 years off-treatment) or waitlist control group (mean age 11.82 ± 2.42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…In this study, peer and conduct problems were more common among the survivors than among healthy controls (Hocking et al, 2015;Mendoza et al, 2019). Interestingly, our data confirm previous findings (Ehrhardt et al, 2018;Hocking et al, 2015;Puhr et al, 2019;Tonning Olsson et al, 2020): executive functions, processing speed, and fluid intelligence were correlated with peer problems, and this was associated with poorer health-related quality of life in CC survivors.…”
Section: Cognitive and Psychosocial Functioning And Health-related Qusupporting
confidence: 90%
“…In this study, peer and conduct problems were more common among the survivors than among healthy controls (Hocking et al, 2015;Mendoza et al, 2019). Interestingly, our data confirm previous findings (Ehrhardt et al, 2018;Hocking et al, 2015;Puhr et al, 2019;Tonning Olsson et al, 2020): executive functions, processing speed, and fluid intelligence were correlated with peer problems, and this was associated with poorer health-related quality of life in CC survivors.…”
Section: Cognitive and Psychosocial Functioning And Health-related Qusupporting
confidence: 90%
“…The assessment showed different qualities of the studies: Two studies [ 19 , 20 ] showed a deficient quality, one study low [ 21 ], four studies moderate [ 5 , 22 , 23 , 24 ], and two trials [ 25 , 26 ] showed high quality, according to Cochrane standards.…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies, except for two [ 19 , 20 ], were designed as randomised controlled investigations, in which a computer-based cognitive training was assigned to intervention or control groups. In four studies [ 5 , 22 , 23 , 26 ], the participants were randomised to experimental cognitive training, according to the study protocol or the waiting list group. In comparison, in three studies [ 21 , 24 , 25 ], the enrolled patients were assigned to adaptive- or not-adaptive computer-based training.…”
Section: Resultsmentioning
confidence: 99%
“…20 Furthermore, there is evidence that social and emotional difficulties are known to exist in the paediatric cancer survivor population, these factors are also consistently linked with poorer educational achievement. 23,24 Whilst it is clear from existing literature that paediatric patients undergoing cancer treatment experience a negative impact upon their educational achievement and academic trajectory, findings relevant to the education system within the UK are limited. There are also areas of variation within the existing literature in this field of research that currently hinder the effective synthesis of data and conclusions.…”
Section: Educational Implications Of Cancer and Cancer Treatmentsmentioning
confidence: 99%
“… 20 Furthermore, there is evidence that social and emotional difficulties are known to exist in the paediatric cancer survivor population, these factors are also consistently linked with poorer educational achievement. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%